Budget Participation And Internal Control For Better Quality Financial Statements - Agus Bandiyono (Jurnal Akuntansi, 2020)
This study aims to determine the effect of budgetary participation on the quality of the internal control system's financial statements as a moderating variable. This research is a quantitative research with the respondents are the principal, the vice-principal, the teacher, and the school committee of SMA and SMK throughout Tangerang City. SEM PLS was used to analyze this research data. The data used in this study came from a questionnaire collected using the survey method. The results of this study are that budget participation has a positive and significant effect on the quality of financial reports, while the internal control system as a moderating variable has a strong enough influence on the variable of budget participation in improving the quality of financial reports.